“Race” and Racism in the Journal of the Canadian Historical Association, 1922‑2021 - Walker, James (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2023)
With few exceptions, Journal articles have represented “race” and racism in step with the conventional wisdom of the times. Although “race” as a category of analysis has not been prominently on the agenda for most of the Journal’s one hundred years, the evolution of the concept and its role in Canadian historical interpretation can be discerned through the annual volumes. In the early years, “race” was taken for granted; it was accepted that humankind was divided into fixed groups known as “races,” and that “race” could be a causal factor in history. During and after World War II, there were some challenges to the significance of “race,” and even some denials of its existence altogether. In recent decades, articles in the Journal have begun to recognize the racism deeply embedded in Canadian social and economic structures, and its impact in domestic colonialism and in other forms of sanctioned discrimination. Racism, rather than biological “race,” is now being seen as a factor in Canada’s development. This understanding raises questions about prevailing accounts of Canadian history, with consequent calls for new versions of our collective past.